ESTIMATIVA DAS MÉDIAS DAS TEMPERATURAS MÁXIMAS MENSAIS E ANUAIS DO ESTADO DE SANTA CATARINA - Buriol, Galileo A.; Ferreira, Mário; Estefanel, Valduino; Pignataro, Ione A. B. (Revista do Centro de Ciências Rurais, 2008)
Estudou-se a correlação entre as médias das temperaturas máximas mensais e anuais, a altitude, a longitude e a latitude, com dados de quinze estações meteorológicas do Estado de Santa Catarina e zonas limitrofes. Verificou-se que a latitude tem pouca influência nas médias das temperaturas máximas. Calcularam-se equações de regressão do tipo Y = a + bX1 + cX2 para estimar as médias mensais e anuais das temperaturas máximas em função da altitude e longitude. Os coeficientes de correlação múlltipla entre essas variáveis foram elevados, o que faculta o uso das temperaturas estimadas para locais que não possuem estações meteorológicas.AbstractMultiple correlation among the monthly and annual means of the maximum daily temperatures, altitude, longitude and latitude were studied using data from 15 meteorological stations located both within Santa Catarina and from nearby States. It was verified that latitude had little influence on the means of maximum temperatures. Regression equations of the type Y = a + bX1 + cX2 were computed to estimate the monthly and annual means of the maximum daily temperatures as a function of altitude and longitude. Tre multiple correlation coefficients obtained were high indicating that these mean temperatures can be estimated for locations that are not located near a meteorological station.